2011
DOI: 10.1371/journal.pone.0026000
|View full text |Cite
|
Sign up to set email alerts
|

Timing Specific Requirement of microRNA Function is Essential for Embryonic and Postnatal Hippocampal Development

Abstract: The adult hippocampus consists of the dentate gyrus (DG) and the CA1, CA2 and CA3 regions and is essential for learning and memory functions. During embryonic development, hippocampal neurons are derived from hippocampal neuroepithelial cells and dentate granular progenitors. The molecular mechanisms that control hippocampal progenitor proliferation and differentiation are not well understood. Here we show that noncoding microRNAs (miRNAs) are essential for early hippocampal development in mice. Conditionally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 38 publications
2
54
1
Order By: Relevance
“…Contrary to a recently published study, which found no change in Reelin levels within Nestin-Cre Dicer depleted cortices using histological assays at E15.5 and E18.5 (Li et al, 2011), we show a 3-fold increase in Reelin mRNA levels in Dicer depleted cortex relative to control at E15.5 (Fig. 6A).…”
Section: Resultscontrasting
confidence: 99%
“…Contrary to a recently published study, which found no change in Reelin levels within Nestin-Cre Dicer depleted cortices using histological assays at E15.5 and E18.5 (Li et al, 2011), we show a 3-fold increase in Reelin mRNA levels in Dicer depleted cortex relative to control at E15.5 (Fig. 6A).…”
Section: Resultscontrasting
confidence: 99%
“…For example, convergent miRNA actions might contribute to silence functions that are no longer important, or are dangerous (e.g., oncogenes), and at the same time shift the proteome toward a new equilibrium in other cells (e.g., committed cells). Consistent with the latter scenario, several studies point out that miRNA functions are particularly required for cell fate transitions in developing neocortex [36, 68, 69, 71, 73, 75, 76, 81]. It should also be mentioned that in most cases, we found examples of two miRNAs that converge on a single target gene.…”
Section: Discussionsupporting
confidence: 89%
“…In agreement with this statement, a wide spectrum of defects, such as premature, delayed, or reiterated generation of certain subtypes of neural stem and progenitors cells (both apical or BP), neurons, or glia, has been reported upon dicer deletion in developing neocortex [36, 66, 68, 69, 71, 73, 75, 76, 81]. This evidence strongly supports our initial observation that in developing mouse, neocortex miRNA functions are less required for self-amplification of NSCs/NPCs, but are particularly important during cell-fate transitions [68].…”
Section: Introductionmentioning
confidence: 69%
“…miRNAs are small ribonucleotide molecules (19 -23 nucleotides) that have broad roles in biology, including neuronal segmentation and tissue development (1), and are necessary for the appropriate and correct regulation of a diverse range of gene expression. miRNAs act through post-transcriptional (2,3) interactions with their mRNA targets to control mRNA stability and protein translation (3,4).…”
mentioning
confidence: 99%